.......................................................................................
First look for the fundamental solutions by solving the homogeneous version of the ODE:
![y''+3y'=0](https://tex.z-dn.net/?f=y%27%27%2B3y%27%3D0)
The characteristic equation is
![r^2+3r=r(r+3)=0](https://tex.z-dn.net/?f=r%5E2%2B3r%3Dr%28r%2B3%29%3D0)
with roots
and
, giving the two solutions
and
.
For the non-homogeneous version, you can exploit the superposition principle and consider one term from the right side at a time.
![y''+3y'=2t^4](https://tex.z-dn.net/?f=y%27%27%2B3y%27%3D2t%5E4)
Assume the ansatz solution,
![{y_p}=at^5+bt^4+ct^3+dt^2+et](https://tex.z-dn.net/?f=%7By_p%7D%3Dat%5E5%2Bbt%5E4%2Bct%5E3%2Bdt%5E2%2Bet)
![\implies {y_p}'=5at^4+4bt^3+3ct^2+2dt+e](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%3D5at%5E4%2B4bt%5E3%2B3ct%5E2%2B2dt%2Be)
![\implies {y_p}''=20at^3+12bt^2+6ct+2d](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%27%3D20at%5E3%2B12bt%5E2%2B6ct%2B2d)
(You could include a constant term <em>f</em> here, but it would get absorbed by the first solution
anyway.)
Substitute these into the ODE:
![(20at^3+12bt^2+6ct+2d)+3(5at^4+4bt^3+3ct^2+2dt+e)=2t^4](https://tex.z-dn.net/?f=%2820at%5E3%2B12bt%5E2%2B6ct%2B2d%29%2B3%285at%5E4%2B4bt%5E3%2B3ct%5E2%2B2dt%2Be%29%3D2t%5E4)
![15at^4+(20a+12b)t^3+(12b+9c)t^2+(6c+6d)t+(2d+e)=2t^4](https://tex.z-dn.net/?f=15at%5E4%2B%2820a%2B12b%29t%5E3%2B%2812b%2B9c%29t%5E2%2B%286c%2B6d%29t%2B%282d%2Be%29%3D2t%5E4)
![\implies\begin{cases}15a=2\\20a+12b=0\\12b+9c=0\\6c+6d=0\\2d+e=0\end{cases}\implies a=\dfrac2{15},b=-\dfrac29,c=\dfrac8{27},d=-\dfrac8{27},e=\dfrac{16}{81}](https://tex.z-dn.net/?f=%5Cimplies%5Cbegin%7Bcases%7D15a%3D2%5C%5C20a%2B12b%3D0%5C%5C12b%2B9c%3D0%5C%5C6c%2B6d%3D0%5C%5C2d%2Be%3D0%5Cend%7Bcases%7D%5Cimplies%20a%3D%5Cdfrac2%7B15%7D%2Cb%3D-%5Cdfrac29%2Cc%3D%5Cdfrac8%7B27%7D%2Cd%3D-%5Cdfrac8%7B27%7D%2Ce%3D%5Cdfrac%7B16%7D%7B81%7D)
![y''+3y'=t^2e^{-3t}](https://tex.z-dn.net/?f=y%27%27%2B3y%27%3Dt%5E2e%5E%7B-3t%7D)
is already accounted for, so assume an ansatz of the form
![y_p=(at^3+bt^2+ct)e^{-3t}](https://tex.z-dn.net/?f=y_p%3D%28at%5E3%2Bbt%5E2%2Bct%29e%5E%7B-3t%7D)
![\implies {y_p}'=(-3at^3+(3a-3b)t^2+(2b-3c)t+c)e^{-3t}](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%3D%28-3at%5E3%2B%283a-3b%29t%5E2%2B%282b-3c%29t%2Bc%29e%5E%7B-3t%7D)
![\implies {y_p}''=(9at^3+(9b-18a)t^2+(9c-12b+6a)t+2b-6c)e^{-3t}](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%27%3D%289at%5E3%2B%289b-18a%29t%5E2%2B%289c-12b%2B6a%29t%2B2b-6c%29e%5E%7B-3t%7D)
Substitute into the ODE:
![(9at^3+(9b-18a)t^2+(9c-12b+6a)t+2b-6c)e^{-3t}+3(-3at^3+(3a-3b)t^2+(2b-3c)t+c)e^{-3t}=t^2e^{-3t}](https://tex.z-dn.net/?f=%289at%5E3%2B%289b-18a%29t%5E2%2B%289c-12b%2B6a%29t%2B2b-6c%29e%5E%7B-3t%7D%2B3%28-3at%5E3%2B%283a-3b%29t%5E2%2B%282b-3c%29t%2Bc%29e%5E%7B-3t%7D%3Dt%5E2e%5E%7B-3t%7D)
![9at^3+(9b-18a)t^2+(9c-12b+6a)t+2b-6c-9at^3+(9a-9b)t^2+(6b-9c)t+3c=t^2](https://tex.z-dn.net/?f=9at%5E3%2B%289b-18a%29t%5E2%2B%289c-12b%2B6a%29t%2B2b-6c-9at%5E3%2B%289a-9b%29t%5E2%2B%286b-9c%29t%2B3c%3Dt%5E2)
![-9at^2+(6a-6b)t+2b-3c=t^2](https://tex.z-dn.net/?f=-9at%5E2%2B%286a-6b%29t%2B2b-3c%3Dt%5E2)
![\implies\begin{cases}-9a=1\\6a-6b=0\\2b-3c=0\end{cases}\implies a=-\dfrac19,b=-\dfrac19,c=-\dfrac2{27}](https://tex.z-dn.net/?f=%5Cimplies%5Cbegin%7Bcases%7D-9a%3D1%5C%5C6a-6b%3D0%5C%5C2b-3c%3D0%5Cend%7Bcases%7D%5Cimplies%20a%3D-%5Cdfrac19%2Cb%3D-%5Cdfrac19%2Cc%3D-%5Cdfrac2%7B27%7D)
![y''+3y'=\sin(3t)](https://tex.z-dn.net/?f=y%27%27%2B3y%27%3D%5Csin%283t%29)
Assume an ansatz solution
![y_p=a\sin(3t)+b\cos(3t)](https://tex.z-dn.net/?f=y_p%3Da%5Csin%283t%29%2Bb%5Ccos%283t%29)
![\implies {y_p}'=3a\cos(3t)-3b\sin(3t)](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%3D3a%5Ccos%283t%29-3b%5Csin%283t%29)
![\implies {y_p}''=-9a\sin(3t)-9b\cos(3t)](https://tex.z-dn.net/?f=%5Cimplies%20%7By_p%7D%27%27%3D-9a%5Csin%283t%29-9b%5Ccos%283t%29)
Substitute into the ODE:
![(-9a\sin(3t)-9b\cos(3t))+3(3a\cos(3t)-3b\sin(3t))=\sin(3t)](https://tex.z-dn.net/?f=%28-9a%5Csin%283t%29-9b%5Ccos%283t%29%29%2B3%283a%5Ccos%283t%29-3b%5Csin%283t%29%29%3D%5Csin%283t%29)
![(-9a-9b)\sin(3t)+(9a-9b)\cos(3t)=\sin(3t)](https://tex.z-dn.net/?f=%28-9a-9b%29%5Csin%283t%29%2B%289a-9b%29%5Ccos%283t%29%3D%5Csin%283t%29)
![\implies\begin{cases}-9a-9b=1\\9a-9b=0\end{cases}\implies a=-\dfrac1{18},b=-\dfrac1{18}](https://tex.z-dn.net/?f=%5Cimplies%5Cbegin%7Bcases%7D-9a-9b%3D1%5C%5C9a-9b%3D0%5Cend%7Bcases%7D%5Cimplies%20a%3D-%5Cdfrac1%7B18%7D%2Cb%3D-%5Cdfrac1%7B18%7D)
So, the general solution of the original ODE is
![y(t)=\dfrac{54t^5 - 90t^4 + 120t^3 - 120t^2 + 80t}{405}\\\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,\,-\dfrac{3t^3+3t^2+2t}{27}e^{-3t}-\dfrac{\sin(3t)+\cos(3t)}{18}](https://tex.z-dn.net/?f=y%28t%29%3D%5Cdfrac%7B54t%5E5%20-%2090t%5E4%20%2B%20120t%5E3%20-%20120t%5E2%20%2B%2080t%7D%7B405%7D%5C%5C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C%5C%2C-%5Cdfrac%7B3t%5E3%2B3t%5E2%2B2t%7D%7B27%7De%5E%7B-3t%7D-%5Cdfrac%7B%5Csin%283t%29%2B%5Ccos%283t%29%7D%7B18%7D)
Answer:
5 tons
Step-by-step explanation: